Illiberalism, populism and democracy in East and West - Wolfgang Merkel; Felix Scholl (Politologický časopis - Czech Journal of Political Science, 2018)
The emergence and persistence of right-wing populist parties (RWPs) in almost all advanced democracies in Eastern Europe, Western Europe, and across the Atlantic is a result of a new cleavage that revolves around the question of how open borders should be for goods, services, capital, migrants, refugees, human rights, and the transfer of political power to supranational institutions: Cosmopolitans opt for opening the nation states' borders, while communitarians prefer more closed and controlled borders in a broader sense. An economic and cultural-discursive representation gap on the communitarian side allowed RWPs to enter the political stage along this cleavage. The composition of their electorate, their thematic focus and their discourse support our hypothesis. We demonstrate that whether RWPs pose a danger for democracy crucially depends on whether they are in government or opposition and whether the context is that of well-established or less consolidated democracies. We also discuss whether polarization is deemed harmful to democracy. RWPs can indeed have a positive impact on a re-intensified political participation. However, if the illiberalism of RWPs dominates policies, politics, and the political discourse in less consolidated democracies, such as in Hungary and Poland, liberal democracy is in danger.
Keywords: 330; cleavage; right-wing populism; communitarianism; cosmopolitanism; illiberal democracy; discourse